Pre-service and Novice Teacher Self-Efficacy: A Tool to Understand and Further Develop Confidence for Impacting Change - Kimberly McDowell; Ashlie Jack; Jeri Carroll; Janice Ewing (The Advocate, 2014)
Teacher efficacy measures a teacher’s perception of his or her capacity as a teacher and impacts teacher behavior in a number of different ways. This study examined teacher efficacy as well as pedagogical beliefs/practices in pre-service and novice in-service teachers to determine the nature of the relationship between the two. Results indicated that the novice in-service teachers demonstrated statistically significant higher scores on the efficacy measure. In regards to the relationship between pedagogy and efficacy, there was no statistically significant relation among the pre-service teachers but with the novice in-service teachers, efficacy was statistically significantly correlated with general instructional pedagogy.